Pola Komunikasi Tim Produksi dalam Alur Kerja Kreatif yang Dimediasi Teknologi di FitAcademy - Permana, Muhammad Fakhri Rizqullah; Priatna, Wahyu Budi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Good communication is crucial in creative production teams. This study examines the communication patterns of the edutech team FitAcademy, which faced internal communication challenges. This study aims to identify communication patterns vertical/horizontal and the mediating role of technology in the workflow. A qualitative case study method was used. Primary data were obtained through participant observation researcher as Video Editor and in-depth interviews with informants CEO, Teacher, Editor selected via purposive sampling. Data analysis utilized the Miles and Huberman model, reduction, display, conclusion. Results show vertical patterns CEO to Team operate via directives and weekly reviews. Horizontal patterns Teacher and Editor are intensive, using face-to-face contact and Google Docs collaboration. The workflow is highly mediated by technology CapCut, AI, Canva.
Keywords: Creative Workflow; Technology Mediation; Communication Patterns